Cervical lymphatic malformations amenable to transhairline robotic surgical excision in children: A case series. Issue 37 (17th September 2021) - Lin, Han-Jie; Lin, Frank Cheau-Feng; Yang, Tsung-Lin; Chang, Chun-Hsiang; Kao, Chia-Hui; Tsai, Stella Chin-Shaw
Abstract : Abstract: Lymphatic malformations are rare benign malformations that predominantly occur in the head and neck region. The advent of surgical robots in head and neck surgery may provide beneficial outcomes for pediatric patients. Here, we describe our experiences with transhairline incisions for robot-assisted surgical resection of cervical lymphatic malformations in pediatric patients. In this prospective longitudinal cohort study, we recruited consecutive patients under 18 years of age who were diagnosed with congenital cervical lymphatic malformations and scheduled for transhairline approach robotic surgery at a single medical center. We documented the docking times, console times, surgical results, complications, and postoperative follow-up outcomes. The studied patients included 2 with mixed-type lymphatic malformations and 2 with macrocystic-type lymphatic malformations. In all 4 patients, the incision was hidden in the hairline; the incision length was <5 cm in 3 patients but was extended to 6 cm in 1 patient. Elevating the skin flap and securely positioning it with Yang retractor took <1 hour in all cases. The mean docking time was 5.5 minutes, and the mean console time was 1 hour and 46 minutes. All 4 surgeries were completed endoscopically with the robot. The average total drainage volume in the postoperative period was 21.75 mL. No patients required tracheotomy or nasogastric feeding tubes. Neither were adverse surgery-associated neurovascular sequelae observed. All 4 patients were successfully treated for their lymphatic malformations, primarily with robotic surgical excisions. Cervical lymphatic malformations in pediatric patients could be accessed, properly visualized, and safely resected with transhairline-approach robotic surgery. Transhairline-approach robotic surgery is an innovative method for meeting clinical needs and addressing esthetic concerns.